2012
DOI: 10.1176/appi.focus.10.3.346
|View full text |Cite
|
Sign up to set email alerts
|

Severe Mood Dysregulation, Irritability, and the Diagnostic Boundaries of Bipolar Disorder in Youths

Abstract: In recent years, increasing numbers of children have been diagnosed with bipolar disorder. In some cases, children with unstable mood clearly meet current diagnostic criteria for bipolar disorder, and in others, the diagnosis is unclear.Severe mood dysregulation is a syndrome defined to capture the symptomatology of children whose diagnostic status with respect to bipolar disorder is uncertain, that is, those who have severe, nonepisodic irritability and the hyperarousal symptoms characteristic of mania but wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 104 publications
4
51
0
1
Order By: Relevance
“…In the case of BD, patients had to have a mania episode as defined by the DSM-IV, including cardinal symptoms such as euphoric mood and grandiosity for at least 4 days (or less if hospitalisation was needed). By doing so, patients who presented severe mood dysregulation and not BD [90] were not included and all patients were euthymic. Finally, using actigraphy as an ambulatory assessment, we were able to examine sleepwake patterns as they occur in naturalistic environments.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of BD, patients had to have a mania episode as defined by the DSM-IV, including cardinal symptoms such as euphoric mood and grandiosity for at least 4 days (or less if hospitalisation was needed). By doing so, patients who presented severe mood dysregulation and not BD [90] were not included and all patients were euthymic. Finally, using actigraphy as an ambulatory assessment, we were able to examine sleepwake patterns as they occur in naturalistic environments.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding misdiagnosis, the samples diagnosed by the Massachusetts General Hospital group (data collected by the authors of this article) have been described as deviating from "classic" presentations of bipolar I disorder by allowing "severe, nonepisodic irritability" to qualify for the mood criterion (72). It is more accurate to describe the Massachusetts General Hospital pediatric bipolar I samples as including patients who meet DSM-IV criteria by having distinct episodes of severe irritable mood lasting 1 week or longer on a background of chronic psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…While most children with DMDD meet criteria for ODD, only 20-40 % of children with ODD meet criteria for DMDD [7]. Of note, some studies have demonstrated pathophysiological differences between DMDD and other diagnoses [12] supporting the standing of DMDD as a unique psychiatric disorder.…”
Section: Disruptive Mood Dysregulation Disorder: Definition Prevalenmentioning
confidence: 99%